Object Interaction and Walking: Integration of Old and New Skills in Infant Development. (7th April 2019) - Heiman, Carli M.; Cole, Whitney G.; Lee, Do Kyeong; Adolph, Karen E.
Abstract : Manual skills such as reaching, grasping, and exploring objects appear months earlier in infancy than locomotor skills such as walking. To what extent do infants incorporate an old skill (manual actions on objects) into the development of a new skill (walking)? We video recorded 64 sessions of infants during free play in a laboratory playroom. Infants' age (12.7–19.5 months), walking experience (0.5–10.3 months), and walking proficiency (speed, step length, etc.) varied widely. We found that the earlier developing skills of holding and exploring objects were immediately incorporated into the later developing skill of walking. Although holding incurred a reliable cost to infants' gait patterns, holding and exploring objects in hand were relatively common activities and did not change with development. Moreover, holding objects was equally common in standing and walking. However, infants did not interact with objects indiscriminately: Object exploration was more frequent while standing than walking, and infants selectively chose lighter objects to carry and explore. Findings suggest that the earlier appearance of some skills may serve to motivate and enrich later appearing skills.